(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the polysemy in Polish linguistic terminology, analyses the reasons of appearing polysemy in Polish linguistic terms, and their major types are defined. The specificity of semantic structure of polysemantic linguistic terms in Polish explanatory and terminological dictionaries is determined.